2012
DOI: 10.1007/978-94-007-4525-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Megabase Replication Domains Along the Human Genome: Relation to Chromatin Structure and Genome Organisation

Abstract: In higher eukaryotes, the absence of specific sequence motifs, marking the origins of replication has been a serious hindrance to the understanding of (i) the mechanisms that regulate the spatio-temporal replication program, and (ii) the links between origins activation, chromatin structure and transcription. In this chapter, we review the partitioning of the human genome into megabased-size replication domains delineated as N-shaped motifs in the strand compositional asymmetry profiles. They collectively span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 90 publications
1
24
0
Order By: Relevance
“…The additional observation of a remarkable gene organization inside these domains with a significant enrichment of expressed genes nearby the bordering “master” replication origins [92], [102] sheds light on these U/N-domains as regions of highly coordinated regulation of transcription and replication by the chromatin structure. These structural and functional units are conserved in mouse [91], [92] and are robust to chromosome rearrangements [103] which indicates that they are likely to be a major determinant of genome evolution [104].…”
Section: Introductionmentioning
confidence: 99%
“…The additional observation of a remarkable gene organization inside these domains with a significant enrichment of expressed genes nearby the bordering “master” replication origins [92], [102] sheds light on these U/N-domains as regions of highly coordinated regulation of transcription and replication by the chromatin structure. These structural and functional units are conserved in mouse [91], [92] and are robust to chromosome rearrangements [103] which indicates that they are likely to be a major determinant of genome evolution [104].…”
Section: Introductionmentioning
confidence: 99%
“…These four main chromatin states were further shown to correlate with MRT, namely from early to late replicating, a transcriptionally active euchromatin state (C1) enriched in insulator binding protein CTCF, a polycomb repressed facultative heterochromatin state (C2), a silent heterochromatin state (C3) not enriched in any available marks and a HP1-associated heterochromatin state (C4). When mapping these chromatin states inside the megabase-sized U-domains Audit et al 2012Audit et al , 2013, where the MRT is U-shaped and its derivative Nshaped like the nucleotide compositional asymmetry in the germline skew N-domains (Brodie of Brodie et al 2005;Touchon et al 2005;Audit et al 2007;Huvet et al 2007;Audit et al 2009;Baker et al 2010;Chen et al 2011;, we have shown that in these replication domains that cover about 50% of the human genome, the replication wave ) proceeds along a directional path through the four chromatin states, from the open euchromatin state C1 at U/N-domain borders successively followed by the three silent chromatin states C2, C3 and C4 at the U/N-domain centers . The complete analysis, of the other half of the genome that is complementary to U-domains ) has confirmed the dichotomic picture proposed in early studies in mouse (Farkash-Amar et al 2008;Hiratani et al 2008Hiratani et al , 2010 and human (Desprat et al 2009;Ryba et al 2010;Yaffe et al 2010) genomes, where early and late replicating regions occur in separated compartments of open and closed chromatin, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A similar gene organization has been observed in the mouse genome Huvet et al, 2007;Baker et al, 2010;Zaghloul et al, 2012) suggesting that skew-N domains are functional domains likely conserved in mammalian genomes. The analysis of genome wide MRT data in seven human cell types including embryonic stem cells (ESC), somatic and HeLa cells has confirmed that a significant number of N-domain borders harbor early initiation zones active in the germline as well as in ESC and somatic cells lines (about 2/3 are active in at least another cell line) Huvet et al, 2007;Audit et al, 2007Audit et al, , 2012Baker et al, 2012a). Even more remarkable, a significant overlap is observed between the skew-N domains and the so-called replication timing MRT U-domains identified as covering about half of the human genome in each of these seven cell types (Baker et al, 2012a;Audit et al, 2012Audit et al, , 2013.…”
Section: Introductionmentioning
confidence: 85%
“…The analysis of genome wide MRT data in seven human cell types including embryonic stem cells (ESC), somatic and HeLa cells has confirmed that a significant number of N-domain borders harbor early initiation zones active in the germline as well as in ESC and somatic cells lines (about 2/3 are active in at least another cell line) Huvet et al, 2007;Audit et al, 2007Audit et al, , 2012Baker et al, 2012a). Even more remarkable, a significant overlap is observed between the skew-N domains and the so-called replication timing MRT U-domains identified as covering about half of the human genome in each of these seven cell types (Baker et al, 2012a;Audit et al, 2012Audit et al, , 2013. In these Mb-sized domains, the MRT has a characteristic U-shape and its derivative is N-shaped like the nucleotide compositional asymmetry in the germline skew-N domains.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation